Designing for Home-Based Work – Lessons from Two English Villages. Issue 1 (2nd January 2017) - Holliss, Frances
Abstract: Contemporary home-based work is generally either invisible or ignored, despite the fact that almost one in three members of the working population in the most rural areas in England now works at or from home and home-based businesses are the driving force in many rural economies. Asking how design could support or develop this aspect of rurality, this paper draws on an ethnographic/architectural study of the lives and premises of home-based workers in two villages in investigating the extent to which the idea of extended fungibility might apply in each location.